2010
DOI: 10.1002/ange.201003172
|View full text |Cite
|
Sign up to set email alerts
|

Entropy‐Controlled Catalytic Asymmetric 1,4‐Type Friedel–Crafts Reaction of Phenols Using Conformationally Flexible Guanidine/Bisthiourea Organocatalyst

Abstract: One of the most important aspects of protein function is the motion that occurs in response to substrate binding. [1] In the dynamics of enzyme catalysis, multiple weak hydrogenbonding interactions [2] in the polypeptide that are controlled by interrelated enthalpy and entropy changes play a significant role in governing the conformational changes that take place. [3] In contrast, the development of asymmetric organocatalysts has rarely focused on hydrogen-bond donors [4][5][6][7][8] that have conformationall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 67 publications
0
30
0
1
Order By: Relevance
“…methyl and ethyl groups)24. It is also noted that the calculated differences in activation free energies of these transition states were similar to those in activation enthalpies, suggesting that the observed selectivities are not due to the entropic control in Sohtome and Nagasawa's systems4247.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…methyl and ethyl groups)24. It is also noted that the calculated differences in activation free energies of these transition states were similar to those in activation enthalpies, suggesting that the observed selectivities are not due to the entropic control in Sohtome and Nagasawa's systems4247.…”
Section: Resultsmentioning
confidence: 58%
“…Moreover, for pTS-I , the α-C-H bonds (to the ammonium group and to the indole ring) are in proximity (2.1 to 2.4 Å) with the ester carbonyl oxygen (Figure 4), alluding to the possibility of the formation of a non-classical C-H δ+ …O δ− binding pocket. Such secondary interactions have been observed to play an important role in molecular recognition and stereoselective catalytic processes414243. To confirm that such short bond distances are result of hydrogen bonding interactions rather than simple steric arrangement, two-center Mayer bond order analysis44 was carried out.…”
Section: Resultsmentioning
confidence: 99%
“…[23d] As seen by inspecting the data in Table 3, both enthalpy (DDH°) and entropy (DDS°) compensation govern the stereodetermining step of solvent-dependent organocatalytic reactions promoted by 1 a. In contrast, negative values of DDH°R -S and DDS°R -S control the stereodiscrimination processes in R-selective reactions in aprotic polar solvents (Table 3, entries [5][6][7][8], in which the DDH°R -S term has a major influence on lowering the DDG°R -S in the R-selective reactions. In these cases, differential activation entropies (DDS°S -R ) contribute to lowering the DDG°S -R of reactions having unfavorable enthalpic contributions.…”
Section: Methodsmentioning
confidence: 99%
“…

Hydrogen bonding promoted asymmetric catalysis has rapidly grown over the past decade. [8] A new perspective described herein concerns the possibility of bringing about dynamic control of the stereochemical outcomes in the organocatalytic system by tuning the enthalpy and entropy related external factors (e.g., reaction solvents, the substrate concentration, and pressure). [2] In contrast, recent findings from our group have shown that conformationally flexible guanidine/bisthiourea organocatalysts 1 [3][4][5][6][7] display unique stereodiscrimination processes that are governed by differential activation entropy (DDS°= 25.4 J mol À1 K À1 ) rather than differential activation enthalpy (DDH°=~0 kJ mol À1 ) in ortho-and enantioselective 1,4-type Friedel-Crafts alkylations of sesamol.

…”
mentioning
confidence: 99%
See 1 more Smart Citation